2020
DOI: 10.1186/s12936-020-03356-9
|View full text |Cite
|
Sign up to set email alerts
|

A cluster randomized trial of delivery of intermittent preventive treatment of malaria in pregnancy at the community level in Burkina Faso

Abstract: Background: Malaria in pregnancy is responsible for 8-14% of low birth weight and 20% of stillbirths in sub-Saharan Africa. To prevent these adverse consequences, the World Health Organization recommends intermittent preventive treatment of pregnant women (IPTp) with sulfadoxine-pyrimethamine be administered at each ANC visit starting as early as possible in the second trimester. Global IPTp coverage in targeted countries remains unacceptably low. Community delivery of IPTp was explored as a means to improve c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 22 publications
(31 reference statements)
0
16
0
Order By: Relevance
“…One option to increase IPTp-SP coverage is community delivery by community health workers, rather than ANC. This delivery route has been shown in a clinical trial in Burkina Faso to increase IPTp-SP compliance from 2.1 to 2.8 doses in the community delivery study arm with no apparent decrease in ANC attendance [ 46 ]. Seven women reported receiving IPTp-SP despite being in the first trimester.…”
Section: Discussionmentioning
confidence: 99%
“…One option to increase IPTp-SP coverage is community delivery by community health workers, rather than ANC. This delivery route has been shown in a clinical trial in Burkina Faso to increase IPTp-SP compliance from 2.1 to 2.8 doses in the community delivery study arm with no apparent decrease in ANC attendance [ 46 ]. Seven women reported receiving IPTp-SP despite being in the first trimester.…”
Section: Discussionmentioning
confidence: 99%
“…Despite long-standing recommendations, IPTp coverage has lagged, leading to efforts to explore more efficient delivery models such as community-based delivery [ 14 , 15 ]. This intervention in Burkina Faso, as described in Gutman et al was found to increase IPTp, to not reduce ANC visits [ 20 ] as had occurred in several other studies delivering c-IPTp [ 23 , 24 ], and to be a safe and acceptable delivery model both from the perspectives of CHWs and facility HCWs.…”
Section: Discussionmentioning
confidence: 99%
“…To address the challenge of low IPTp uptake, the Burkina Faso government, with support from the U.S. President’s Malaria Initiative (PMI), conducted a cluster-randomized trial to determine the effect of community based IPTp (c-IPT) distribution on IPTp uptake and ANC coverage [ 20 ]. The intervention involved training existing CHWs to implement community sensitization activities around antenatal care (ANC) and malaria in pregnancy, and to refer pregnant women to ANC for their first dose of IPTp.…”
Section: Introductionmentioning
confidence: 99%
“…Similar trials increased IPTp2+ uptake in Uganda by 37.3 percentage points and IPTp3+ uptake in Burkina Faso by 17.6 percentage points [12,13]. The impact on ANC attendance was variable, with a statistically signi cant increase in number of visits in Uganda, but no effect in Nigeria or Burkina Faso [11][12][13]. Trials in Uganda and Malawi that focused exclusively on training CHWs for IPTp delivery without emphasizing ANC referrals also led to increased IPTp2+ uptake (27.6 and 29.3 percentage points, respectively), but ANC attendance decreased (19.3 and 17.9 percentage points, respectively) [14,15].…”
mentioning
confidence: 91%
“…A cluster randomized controlled trial in Nigeria found that training CHWs to deliver IPTp and provide ANC referrals increased the proportion of pregnant women taking IPTp2+ by 35.3 percentage points [11]. Similar trials increased IPTp2+ uptake in Uganda by 37.3 percentage points and IPTp3+ uptake in Burkina Faso by 17.6 percentage points [12,13]. The impact on ANC attendance was variable, with a statistically signi cant increase in number of visits in Uganda, but no effect in Nigeria or Burkina Faso [11][12][13].…”
mentioning
confidence: 96%